COVID‐19 and the Uncovering of Health Care Disparities in the United States, United Kingdom and Canada: Call to Action. Issue 10 (24th August 2021) - Ala, Aftab; Wilder, Julius; Jonassaint, Naudia L.; Coffin, Carla S.; Brady, Carla; Reynolds, Andrew; Schilsky, Michael L.
Abstract : The coronavirus disease 2019 (COVID‐19) pandemic created a crisis that disproportionately affected populations already disadvantaged with respect to access to health care systems and adequate medical care and treatments. Understanding how and where health care disparities are most widespread is an important starting point for exploring opportunities to mitigate such disparities, especially within our patient population with liver disease. In a webinar in LiverLearning, we discussed the impact of the pandemic on the United States, United Kingdom and Canada, highlighting the disproportionate effects on infection rates and death for certain ethnic minorities, those socioeconomically disadvantaged and living in higher density areas, and those working in health care and other essential jobs. We set forth a "call to action" for members of the American Association for the Study of Liver Diseases and the larger community of providers of liver disease care to generate viable solutions to improve access to care and vaccination rates of our patients against COVID‐19, and in general help reduce health care disparities and improve the health of disadvantaged populations within their communities. Solutions will likely involve personalized interventions and messaging for communities that honor local leaders and embrace the diverse needs and different cultural sensitivities of our unique patient populations.